STUDI FENOMENOLOGI: PERAN GENDER DALAM PELAKSANAAN TRADISI KEAGAMAAN UNTUK MENJAGA KEARIFAN LOKAL DI DESA KUBUTAMBAHAN - Putu Agus Windu Yasa Bukian; I Wayan Sujana (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2024)
Gender inequality is the issue most frequently discussed at every meeting in every field. In particular, gender inequality is carried out under the pretext of implementing a religious tradition or maintaining local wisdom. The aim of this research is to conduct a phenomenological study of gender roles in the implementation of religious traditions in Kubucepatn Village. This research method uses a qualitative study with a phenomenological approach. The samples taken were 3 mothers from Kubucepatn Village, 1 village head, 1 trusted community religious figure. This research took 1 month with data collection techniques using in-depth interviews and the instrument used an interview guide. The results of the research were further analyzed using a thematic review and then triangulation was carried out. The research results found that there were 3 big themes found in this research, namely patrilineal culture, maintaining traditions and income as a trigger for happiness. The conclusion is that there are 3 major themes found in the phenomenological study in Kubuaddan Village.